2016
DOI: 10.1038/srep19034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body mass index on the performance characteristics of PSA-related markers to detect prostate cancer

Abstract: To examine whether the predictive performance of prostate-specific antigen (PSA) and PSA-related markers for prostate cancer (PCa) is modified by body mass index (BMI). Patients with a PSA 2–10 ng/mL who underwent multicore prostate biopsies were recruited from three tertiary centers. Serum markers measured included total PSA (tPSA), free-to-total PSA (f/tPSA), p2PSA, percentage of p2PSA (%p2PSA), and prostate health index (PHI). The association between serum markers and PCa risk was assessed by logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…For all tested markers, the predictive value of cancer risk was lower in obese patients than in normal-weight patients. 11 In our study, there was no remarkable correlation between PSA concentration and BW/BMI (Supplementary Table 3, http://links.lww.com/JCMA/ A258).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…For all tested markers, the predictive value of cancer risk was lower in obese patients than in normal-weight patients. 11 In our study, there was no remarkable correlation between PSA concentration and BW/BMI (Supplementary Table 3, http://links.lww.com/JCMA/ A258).…”
Section: Discussioncontrasting
confidence: 47%
“…Also, compared to normal-weight men, the PSA concentration of overweight men was 3.43% lower, and obese men were 12.9% lower. 10 A study conducted by Zhu et al 11 revealed 516 men, of whom 18.2% had PCA at biopsy. For all tested markers, the predictive value of cancer risk was lower in obese patients than in normal-weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, PSA is a prostate-specific but not a Pca -specific marker. [ 5 ] The human body can synthesize PSA not only confined to the Pca tissue, but also including normal prostate tissue, many studies have pointed out that all disease destroy prostate epithelial cells can cause elevated PSA in the blood, but PSA rise more apparent in patients with Pca, which leads to PSA as markers for diagnosis of Pca has a high misdiagnosis rate, especially in the PSA ”grey area” (4–10 ng/mL) patients. When PSA is 4 to 10 ng/mL, specificity rate is only 48.6%, with 50% of the rate of misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The need for the constant improvement of the diagnostics tools is given, for example, by a recently established effect of obesity (measured in terms of the body mass index) on the predictive performance of the well-established and widely used biomarker, prostate-specific antigen (PSA), and PSA-related markers for prostate cancer. 2 These and similar facts alone should be sufficient to spark the scientific community's interest in studying more on possible causes of this very common male disease. Sometimes, a new approach needs to be taken to further the advancements in biomedical research.…”
Section: Introductionmentioning
confidence: 98%
“…Although there has been progress in the detection and treatment of prostate cancer, it is clear that more research is needed to make the diagnosis more reliable. The need for the constant improvement of the diagnostics tools is given, for example, by a recently established effect of obesity (measured in terms of the body mass index) on the predictive performance of the well-established and widely used biomarker, prostate-specific antigen (PSA), and PSA-related markers for prostate cancer 2. These and similar facts alone should be sufficient to spark the scientific community's interest in studying more on possible causes of this very common male disease.…”
Section: Introductionmentioning
confidence: 99%